Upaya pedagang dalam meningkatkan pendapatannya di Pasar Tradisional Sabtu - Zachra, Annisa Nabila; Ramadhan, Anggia (Journal of Economics Research and Policy Studies, 2025)
The traditional Saturday market in Buntu Bedimbar Village is one of the centers of economic activity for the village community. However, fierce competition among traders and limited capital have led to income inequality. Traders are required to implement appropriate strategies to increase their income, including through competitive pricing, improving product quality, and extending working hours. This situation highlights the need for research to understand the extent to which these efforts affect traders' income. This study employs a quantitative approach using a questionnaire distributed to 96 vendors at the Saturday Traditional Market. Data were analysed using multiple linear regression to examine the impact of competitive pricing, product quality, and working hours on vendor income. The results of the study indicate that, both partially and simultaneously, the variables of competitive pricing, product quality, and working hours do not significantly affect the income of vendors at the Saturday Traditional Market. The implication is that increasing the income of traditional market traders is not sufficient only through price, quality and working hour strategies, but requires a more holistic and contextual approach.